Are Aboriginal people more likely to be diagnosed with more advanced cancer?. Issue 4 (2nd March 2015) - Gibberd, Alison; Supramaniam, Rajah; Dillon, Anthony; Armstrong, Bruce K; O'Connell, Dianne L
Abstract: Objective: To determine whether Aboriginal people in New South Wales were diagnosed with more advanced cancer than non‐Aboriginal people. Design, setting and participants: Cross‐sectional study of cancer cases, excluding lymphohaematopoietic cancers and cancers of unknown primary site, diagnosed in NSW in 2001–2007. Main outcome measure: Spread of disease at time of cancer diagnosis. Results: Overall, 40.3% of 2039 cancers in Aboriginal people and 46.6% of 191 954 cancers in non‐Aboriginal people were localised at diagnosis. After adjusting for age, sex, year of diagnosis, area of residence and socioeconomic status, Aboriginal people had significantly higher risks of regional or distant spread for head and neck cancer, relative to localised spread, than non‐Aboriginal people (regional: adjusted relative risk ratio [RRR], 1.89; 95% CI, 1.21–2.98; distant: adjusted RRR, 3.40; 95% CI, 1.85–6.05; P < 0.001). For breast, cervical and prostate cancers and melanoma, the risks of regional or distant spread were higher for Aboriginal people, but these differences were not statistically significant. For lung, colorectal, upper gastrointestinal tract, other gynaecological, and eye, brain and central nervous system cancers, the risks of regional, distant and unknown spread of cancer were similar for Aboriginal and non‐Aboriginal people. Conclusion: Aboriginal people were more likely than non‐Aboriginal people to be diagnosed with more advanced cancer for only a few cancer types, most notably head and neck cancers. Differences in spread of disease at diagnosis are unlikely to explain much of the survival differences observed across a wide range of cancers between Aboriginal and non‐Aboriginal people in NSW.